The Effect of Project-Based Learning (PjBL) on Mathematical Logic Learning Results - Rezkiyana Hikmah; Lin Suciani Astuti; Noni Selvia (Cita konsultindo, 2025)
This research is motivated by the fact that many students still have difficulties in mastering mathematical logic, one of which is caused by conventional learning methods that are theoretical and do not involve practical activities. This condition is supported by the low initial test results in the discrete mathematics course, where almost 50% of students show difficulty in solving mathematical logic problems. This study aims to analyze the effect of the application of Project-Based Learning (PjBL) on the learning outcomes of mathematical logic in students. The method used in the research is pre-experiment with one group pretest-postest design. The research subjects were 69 students majoring in informatics engineering in Jakarta. The instruments used were math logic pretest and posttest. The results showed that the application of Project-Based Learning affected the learning outcomes of mathematical logic. This can be seen from the increased percentage (P) which is 72.95% (pretest) and 86.84% (posttest). The results of statistical hypothesis testing with the Wilcoxon test obtained a sig value of 0.000 <0.05 which means that there is an increase in students' mathematical logic learning outcomes. PjBL has a significant effect on students' math logic learning outcomes.